Passivation Layers of Ultra-Advanced High Strength Steels and High Strength Steels - REBECCA DEWFALL (2024)
The fundamental ambition of this thesis is to assess the effects of chemical com-position, temperature and elapsed time reaction on scale formation. The control of oxidation rates and oxide morphology are focal points of interest along with the evolution and formation mechanisms of scale morphology with time and temperature.An approach using rapid alloy prototyping (RAP) was selected to help discern the effects of common alloying elements Mn, Si and Mo, on overall scale formation using a wt% comparable to that seen in high strength industrial grades. RAP was successfully used to investigate the formation of oxides associated with Mn, Si and Mo in isolation. The oxide thickness was shown to vary signiﬁcantly depending on the alloying additions. A minimum fundamental addition of 1wt.% Si was requisite in order to produce a complete passivation layer.Industrial steel grades were investigated to predict the oxidation rates, scale formation and blister regimes that may form within the hot-strip mill. New and previously unidentiﬁed blister formation mechanisms were discovered. Blister upon cooling was discovered during air cooling and observed on a number of samples.Unique and new phenomena such as blister crown splitting and secondary blister were identiﬁed on DP800 due to the presence of a conglomerated spinel phase and hematite in the outer oxide.Plant trials were conducted with differing coiling temperatures after hot rolling to determine the effect on internal oxidation. It was discovered that coiling temperature had a signiﬁcant impact on the depth of internal oxidation after hot rolling, with a strong negative correlation associated between temperature and depth of the internal oxidation zone. The recommended coiling temperature has been implemented in the United Kingdom, Netherlands and India, eliminating issues sur-rounding cleanliness after hot-band annealing.Analysis was conducted using; TGA, EBSD, EDS, WDS, FIB and FEG-SEM imaging.